2020
DOI: 10.1038/s41598-020-69570-2
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of Chlorin e6-PVP (Ce6-PVP) for improved endoscopic detection of neoplastic lesions in a murine colitis-associated cancer model

Abstract: Screening colonoscopy is crucial in reducing the mortality of colorectal cancer. However, detecting adenomas against the backdrop of an inflamed mucosa (e.g. in ulcerative colitis) remains exceedingly difficult. Therefore, we aimed to improve neoplastic lesion detection by employing a fluorescencebased endoscopic approach. We used the well-established murine AOM/DSS model to induce inflammation-driven carcinogenesis in the colon. In our diagnostic approach, we evaluated Chlorin e6 polyvinylpyrrolidone (Ce6-PVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Hence, there are no artefacts which occur as it happens from fibre bundles. This system was used with a spectral filter as a fluorescence endoscope system for the investigation of the topical application of Chlorin e6-PVP for improved endoscopic detection of neoplastic lesions 18 . The set-up is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, there are no artefacts which occur as it happens from fibre bundles. This system was used with a spectral filter as a fluorescence endoscope system for the investigation of the topical application of Chlorin e6-PVP for improved endoscopic detection of neoplastic lesions 18 . The set-up is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1 .
Figure 1 Schematics of the set-up (modified as described in our previous study 18 ). The top schematic shows the overall set-up and the bottom schematic shows the optical set-up which images the light from the endoscope.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodynamic therapy (PDT) is a minimally invasive therapeutic approach that utilizes photosensitizing agents and light activation, resulting in the generation of reactive oxygen species and subsequent tumor destruction [ 3 ]. Chlorin e6 (Ce6), a second-generation photosensitizer, exhibits antitumor activities during photodynamic therapy [ 4 ]. Some studies have indicated that efficiently internalized Ce6 is enriched in the mitochondria and exhibits almost no cytotoxicity under dark conditions but strong photocytotoxicity resulting from reactive oxygen species (ROS) production during photodynamic therapy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%